P53 protein expression in non-Hodgkin's lymphoma. Comparative study with the wild type p53 induced proteins mdm2 and p21/waf1. Issue 5 (October 1996) - Tzardi, M; Kouvidou, Ch; Panayiotides, I; Stefanaki, K; Rontogianni, D; Zois, E; Koutsoubi, K; Eliopoulos, G; Delides, G; Kanavaros, P
Abstract : Aims —To investigate the pattern of expression of p53 protein and two wild type p53 induced proteins (mdm2 and p21/waf1) as an indirect way of assessing p53 gene status in non-Hodgkin's lymphoma. Methods —Formalin fixed, paraffin wax embedded tissue from 87 cases of nodal non-Hodgkin's lymphoma, comprising 52 high grade and 35 low grade tumours, was stained by immunohistochemistry for p53, mdm2 and p21/waf1 proteins. Results—p53, mdm2 and waf1/p21 proteins were expressed in 36/52, 21/52 and 31/52 high grade and 3/35, 21/35 and 3/35 low grade non-Hodgkin's lymphomas, respectively. Parallel p53/mdm2 protein expression was found in 23 cases (21 high grade and two low grade). These 23 cases were also positive for p21/waf1 protein expression. Discordant p53 positive/mdm2 negative protein expression was found in 16 cases (15 high grade and one low grade). Eleven (10 high grade and one low grade) of these 16 cases were p21/waf1 positive and the remaining five high grade non-Hodgkin's lymphomas were p21/waf1 negative. Mdm2 and p21/waf1 proteins were not expressed in the absence of p53 protein expression. Conclusions —p53, mdm2 and waf1/p21 protein expression is more frequently associated with aggressive histotypes of non-Hodgkin's lymphoma. Parallel expression of p53, mdm2 and p21 proteins may represent non-Hodgkin's lymphomas with a wild type p53 gene as mdm2 and p21 proteins can be induced by the wild type gene. In these cases p53 protein expression may result from stabilisation via complex formation with the mdm2 protein. This could be important in the pathogenesis of these cases as mdm2 may deregulate the p53 dependent growth suppressive pathway. Discordant p53 positive/mdm2 negative/p21 negative protein expression may represent non-Hodgkin's lymphoma with p53 gene mutations unable to activate expression of mdm2 and p21 proteins. Non-Hodgkin's lymphoma with p53 positive/mdm2 negative/p21 positive protein expression may have either wild type p53 with deregulated mdm2 gene expression or mutated p53 gene with p53 independent p21 expression.